The durable wheat disease resistance gene Lr34 confers common rust and northern corn leaf blight resistance in maize. Issue 4 (15th November 2016) - Sucher, Justine; Boni, Rainer; Yang, Ping; Rogowsky, Peter; Büchner, Heike; Kastner, Christine; Kumlehn, Jochen; Krattinger, Simon G.; Keller, Beat
Summary: Maize (corn) is one of the most widely grown cereal crops globally. Fungal diseases of maize cause significant economic damage by reducing maize yields and by increasing input costs for disease management. The most sustainable control of maize diseases is through the release and planting of maize cultivars with durable disease resistance. The wheat gene Lr34 provides durable and partial field resistance against multiple fungal diseases of wheat, including three wheat rust pathogens and wheat powdery mildew. Because of its unique qualities, Lr34 became a cornerstone in many wheat disease resistance programmes. The Lr34 resistance is encoded by a rare variant of an ATP‐binding cassette (ABC) transporter that evolved after wheat domestication. An Lr34 ‐like disease resistance phenotype has not been reported in other cereal species, including maize. Here, we transformed the Lr34 resistance gene into the maize hybrid Hi‐II. Lr34 ‐expressing maize plants showed increased resistance against the biotrophic fungal disease common rust and the hemi‐biotrophic disease northern corn leaf blight. Furthermore, the Lr34 ‐expressing maize plants developed a late leaf tip necrosis phenotype, without negative impact on plant growth. With this and previous reports, it could be shown that Lr34 is effective against various biotrophic and hemi‐biotrophic diseases that collectively parasitize all major cereal crop species.